The Economic Impact of the US Unconventional Monetary Policy, Global Commodity Shocks, and Oil Price Shocks on ASEAN 3 - Rifa’i, Khamdan (International Journal of Energy Economics and Policy, 2023)
This study examines the implications of the United States unconventional monetary policy, global commodity prices, and the oil price shock on monetary policy responses and economic growth in the ASEAN 3 countries of Indonesia, Malaysia, and the Philippines. The empirical evidence suggests that the shock from the United States unconventional monetary policy led to the change in ASEAN’s monetary policy. The fluctuation of crude oil and global commodity prices considerably impacts ASEAN’s monetary policy response 3. The Central Bank can use such evidence as a reference to alter monetary policy in reaction to the global oil price and the unconventional monetary policy of the United States. The government will also be able to foresee the impact of global oil and commodities prices and preserve ASEAN 3’s economic growth.